Implementation of Vibration Sensor and Pin Lock using Keypad for Charity Box Security - Ilham, Dirja Nur; Candra, Rudi Arif; Budiansyah, Arie; Sipahutar, Erwinsyah; Harahap, Muhammad Khoiruddin; Anugreni, Fera (International Journal of Multidisciplinary Sciences and Arts, 2023)
Security is a state in which people or things feel safe from ominous or unsettling hazards, which will then cause them to feel at ease and comfortable. There are many ways to achieve security, one of which is via utilizing and deploying technology. The use of security technology has advanced quickly in recent years, from low-tech to high-tech techniques. By using Arduino as a circuit controller to process input from a vibrating sensor and 4x4 keypad, output to a solenoid as a charity box lock, and a buzzer that serves as an alarm in case of theft, technological or automated methods can reduce charity box theft and also increase the security of charity box locks. The charity box security system tool is made to prevent the theft of charity boxes, which frequently happens in mosques. If someone tries to steal the charity box, an alarm will go off, and you need a pin that has been programmed on an Arduino Ide and stored in EEPROM to open the charity box cover, so this tool can stop charity box theft in mosques.